Humanistic and Existential Psychology in the Practice of Psychotherapy - Aureliano Pacciolla (Litbang STFT Widya Sasana Malang, 2019)
In contemporary psychology, the humanistic-existential approach places its center on the sense of life but it should be distinguished from the meaning of life. In this article, after distinguishing the sense form the meaning of life, two specific tools will be considered: Purpose In Life Scale and the Self-Transcendence Scale. Then, other two useful tools will be presented for a clinical intervention: the metacognition functioning (MSAS) and the personality functioning (LPFS). A new proposal to clinicians will be to apply these last two tools in the self-administered form and for the best friend (BF) of the subject; so we can have the self-perception and the perception of others about both, metacognition and personality functioning. Mach more than single items on metacognition and personality functioning, the most relevant to present the basics of the humanistic-existential approach.